Analisis Tingkat Kepuasan Mutu Pelayanan Badan Penyelenggara Jaminan Sosial (BPJS) di RSUD Kota Madya Langsa dengan Model Service Quality (SERVQUAL) - Roy Sari Milda Siregar; Petri Yusrina; Rica Yunita (Jurnal Optimalisasi, 2016)
Analysis of the work program of BPJS can be utilized to determine the applicability of the program to fulfil the needs of the patients as the direct beneficiary of the program. This study is intended to be the basis for management of BPJS, hospital and government to improve the quality of services. The research is a descriptive-qualitative field study and using SERVQUAL method that considers BPJS beneficiary satisfaction in terms of principle, Confidence, Reliability, Tangibility, Empathy and Responsiveness. A total of 30 questionnaires were distributed to the patients of BPJS from diverse educational background, occupation, age and gender. Based on the analysis, patient satisfaction with services obtained by BPJS are as follows: low satisfaction (10%), medium (66,7%) and high (23,3%).Keywords: End-user computing satisfaction, user satisfaction, evaluation of information systems.